2011 IEEE Third International Conference on Privacy, Security, Risk and Trust and 2011 IEEE Third International Conference on S 2011
DOI: 10.1109/passat/socialcom.2011.142
|View full text |Cite
|
Sign up to set email alerts
|

An Agent-Based Model of Epidemic Spread Using Human Mobility and Social Network Information

Abstract: Abstract-The recent adoption of ubiquitous computing technologies has enabled capturing large amounts of human behavioral data. The digital footprints computed from these datasets provide information for the study of social and human dynamics, including social networks and mobility patterns, key elements for the effective modeling of virus spreading. Traditional epidemiologic models do not consider individual information and hence have limited ability to capture the inherent complexity of the disease spreading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 16 publications
0
108
0
2
Order By: Relevance
“…For example, an ABM of 2009 H1N1 outbreak in Mexico showed that government mobility restrictions reduced the spread of the virus by about 10% and postponed it by about 2 days [71]. This policy is in agreement with the recommendation of the World Health Organization, which calls for the suspension of activities in educational, government and business units in case of a pandemic.…”
Section: 'What-if'?mentioning
confidence: 68%
See 1 more Smart Citation
“…For example, an ABM of 2009 H1N1 outbreak in Mexico showed that government mobility restrictions reduced the spread of the virus by about 10% and postponed it by about 2 days [71]. This policy is in agreement with the recommendation of the World Health Organization, which calls for the suspension of activities in educational, government and business units in case of a pandemic.…”
Section: 'What-if'?mentioning
confidence: 68%
“…Humans conveniently produce relevant data as a byproduct of their digital life. Examples include the above-mentioned use of mobility patterns extracted from mobile phone call records to simulate the 2009 H1N1 outbreak in Mexico and to evaluate the impact that government policies had on the spreading of the virus [71], and the use of policy records to simulate the 2011 civil unrest in London [81]. This allows for a "more realistic representation of human behavior which includes the behavioral changes that might take place" during the dynamic under study [71;p.2].…”
Section: Opportunitiesmentioning
confidence: 99%
“…To overcome this limitation, agent based approaches are used widely to model spread of epidemic disease. In agent based modelling (ABM) individual human behaviour [12][13] and its inherent fuzziness are simulated by representing every person as a software agent. In ABM model each agent is characterized with a variety of variables that are related to spread of disease such as social characteristics, socio-economic status, health status, etc.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, from our analysis, we could determine that in areas with lower socio-economic levels it would be easier to contain the epidemic than in areas with higher SEL, where individuals carry out their daily activities in larger geographical areas. It is important to highlight that although these results provide important insights to model and analyze the spreading of specific epidemics (like HIV or flu) many other variables need to be taken into account to build a realistic spread simulation as presented in [19].…”
Section: Implications For Public Policy Designmentioning
confidence: 99%